Repetition and Emotional Closeness in Inclusive Basketball Coaching for Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD): Pengulangan dan Kedekatan Emosional dalam Pelatihan Bola Basket Inklusif bagi Anak dengan Gangguan Spektrum Autisme dan Gangguan Perhatian Hiperaktivitas - Sekar Arum Yulianti Putri Wibowo; Heidy Arviani (Academia Open, 2026)
General Background: Inclusive sports support social interaction, communication, attention, and emotional development in children with Autism Spectrum Disorder and Attention Deficit Hyperactivity Disorder. Specific Background: Basketball requires trainers to adapt communication to diverse attention spans, emotions, and abilities. Knowledge Gap: Limited studies explain interpersonal communication strategies in mixed-group training for children with developmental conditions. Aims: This study analyzes interpersonal strategies and communication barriers during inclusive basketball training. Results: A descriptive qualitative study involved five informants (one head trainer, two assistants, and two parents) using interviews, observation, documentation, and literature review. Data were analyzed with the Miles and Huberman model and triangulation. Four strategies emerged: building rapport, providing motivation, adjusting targets fairly, and repeating instructions. Verbal communication was supported by gestures, demonstrations, eye contact, positive expressions, rewards, and light physical contact. Barriers included mood changes, limited attention, restricted eye contact, communication differences, trainer-student ratios, and trainer experience. Novelty: The study combines relational, motivational, equitable, and repetitive communication strategies in inclusive sports. Implications: Sports academies should provide specialized communication training and strengthen family coordination to support participation and learning continuity. Highlights: Four interpersonal strategies combined rapport, motivation, equitable treatment, plus recurring instruction. Gestures, demonstrations, eye contact, rewards, plus positive reinforcement supplemented verbal messages. Varying attention, mood, communication ability, staffing ratios, plus trainer experience formed principal barriers. Keywords: Autism Spectrum Disorder (ASD), Attention Deficit Hyperctivity Disorder (ADHD), Basketball Coaching, Interpersonal Communication, Inclusive Sports